Associations between the neighbourhood characteristics and body mass index, waist circumference, and waist-to-hip ratio: Findings from Alberta's Tomorrow Project. (July 2020) - Nichani, Vikram; Turley, Liam; Vena, Jennifer E.; McCormack, Gavin R.
Abstract: This study estimated the associations between neighbourhood characteristics and self-reported body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) risk categories among Canadian men and women. Using data from the Alberta's Tomorrow Project (n = 14, 550), we estimated 3- and 4-way intersections, business destinations, population count, and normalized difference vegetation index (NDVI) within a 400 m radius of participant's home. Intersections, business destinations, and population count (z-scores) were summed to create a walkability score. Four-way intersections and walkability were negatively associated with overweight and obesity. Walkability was negatively associated with obesity. NDVI was negatively associated with high-risk WHR and population count and walkability positively associated with high-risk WHR. Among men, population count and walkability were negatively associated with obesity, and business destinations and walkability were negatively associated with overweight and obesity. Among women, NDVI was negatively associated with overweight (including obesity), obesity, and high-risk WC. Interventions promoting healthy weight could incorporate strategies that take into consideration local built environment characteristics. Highlights: Street intersections and walkability were negatively associated with overweight and obesity. Neighbourhood greenness was negatively associated with waist-to-hip ratio. Population count and walkability were positively associated with waist-to-hip ratio. Some built environment-weight associations differed between men and women.